CIN III and cervical SCC with negative oncogenic HPV PCR: A case series. (14th November 2019) - Sturrock, Sam; Griffiths, Andrew; Jobling, Thomas
Abstract : With the recent introduction of the renewed National Cervical Screening Program (NCSP) in Australia, utilising primary human papillomavirus (HPV) nucleic acid testing (NAT) for known oncogenic HPV types rather than cervical cytology, we reflect on three asymptomatic women with negative oncogenic HPV test results and high‐grade cervical abnormalities including cervical intraepithelial neoplasia (CIN) III and cervical squamous cell carcinoma (SCC). The two cases with CIN III had a 'probable' oncogenic subtype (HPV 53) identified on further testing, while the case of SCC had no HPV virus identified. These cases serve as a reminder of the need for ongoing diligence despite low‐risk screening under the new program.